1998
DOI: 10.1007/bf03012702
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular blocking effects of rocuronium during desflurane, isoflurane, and sevoflurane anaesthesia

Abstract: INTERNPurpose: To determine the magnitude of the potentiation of rocuronium by desflurane, isotlurane and sevotturane 1.5 MAC anaesthesia. Methods: In a prospective, randomised, study in 80 patients, the cumulative dose-effect curves for rocuronium were determined during anaesthesia with desflurane, sevoflurane and isoflurane (with N20 700/6, I 5 min steady state) or total intravenous anaesthesia (-i-lVA) using propofol/fentanyl. Neuromuscular block was assessed by acceleromyography CTOF-Guarcl| after t~in-of-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
54
1
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(61 citation statements)
references
References 21 publications
4
54
1
2
Order By: Relevance
“…Therefore, the anesthetic agents administered in our study did not influence the effects of rocuronium. In contrast, inhaled anesthetics, such as sevoflurane, isoflurane, and desflurane, can potentiate the neuromuscular blocking effects of rocuronium, which would decrease the continuous rocuronium infusion dose requirements [23,24]. Further research is needed to investigate whether the our method, as described herein, is effective under conditions of inhaled anesthesia.…”
Section: Discussionmentioning
confidence: 71%
“…Therefore, the anesthetic agents administered in our study did not influence the effects of rocuronium. In contrast, inhaled anesthetics, such as sevoflurane, isoflurane, and desflurane, can potentiate the neuromuscular blocking effects of rocuronium, which would decrease the continuous rocuronium infusion dose requirements [23,24]. Further research is needed to investigate whether the our method, as described herein, is effective under conditions of inhaled anesthesia.…”
Section: Discussionmentioning
confidence: 71%
“…In a study on the effects of isoflurane and desflurane on the neuromuscular blocker effects of rocuronium, Wulf et al [6] found more pronounced TOF T1 depression with desflurane or sevoflurane but did not find any difference in the duration of the block or recovery from block. Basic Clin Sci 2013; 2: 57-64…”
Section: Discussionmentioning
confidence: 98%
“…It is a known fact that inhalation anesthesia produces some neuromuscular relaxation even though not as high as the one with neuromuscular blocker drugs [6,7]. Various studies have been undertaken thinking that volatile anesthetics may be influencing the relaxation effect of neuromuscular blocker drugs when used together and it has been found that several volatile anesthetics affect neuromuscular blocker drugs and that there is no significant difference among these effects [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have found a prolonged T in adults with rocuronium and sevoflurane as compared to isoflurane (26.3 and 14.7 minutes, respectively) 28 . The slower recovery time observed by some authors may be due to lower rocuronium doses or the association of intravenous anesthetics 20,34,35 . Rocuronium recovery time of 19.7 minutes found in our study was not different from that obtained for atracurium, which was 13.1 minutes.…”
mentioning
confidence: 91%
“…A different study has shown a 70% decrease in mivacurium dose in children anesthetized with isoflurane as compared to those anesthetized with halothane 23 . A period of 30 to 45 minutes is taken into account when studying the influence of volatile anesthetics on neuromuscular blockers, that is, enough time for its diffusion in the muscle compartment and to establish a balance among inhaled alveolar, plasma and muscular concentrations 28,[33][34][35] . Sevoflurane was the volatile anesthetic drug used in this study and was administered for more than 30 to 45 minutes.…”
mentioning
confidence: 99%